2001
DOI: 10.1097/00001721-200110000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of isolated calf muscle vein thrombosis with low-molecular-weight heparin

Abstract: There are no data from prospective studies concerning the treatment of isolated calf muscle vein thrombosis (soleal and gastrocnemial muscle veins), found in 20-40% of patients with lower extremity thrombosis of the calf. We investigated the outcome in two cohorts of consecutive patients, the first receiving low-molecular-weight heparin for 10 days at therapeutic doses and compression therapy; the second cohort, compression therapy alone. In patients on therapeutic heparin (n = 52), no progression to deep vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 10 publications
2
74
0
Order By: Relevance
“…2,48 Schwarz et al in 2 subsequent studies reported different results. In the first study, 49 they found few complications in patients receiving therapeutic doses of LMWH for 10 days plus compression therapy vs those receiving compression alone. In the second, 4 no difference in 3-month progression rates was detected in low-risk patients randomized to 10 days of therapeutic LMWH doses and compression therapy or to compression therapy only.…”
Section: What Is Done In Studies and In Clinical Practicementioning
confidence: 99%
“…2,48 Schwarz et al in 2 subsequent studies reported different results. In the first study, 49 they found few complications in patients receiving therapeutic doses of LMWH for 10 days plus compression therapy vs those receiving compression alone. In the second, 4 no difference in 3-month progression rates was detected in low-risk patients randomized to 10 days of therapeutic LMWH doses and compression therapy or to compression therapy only.…”
Section: What Is Done In Studies and In Clinical Practicementioning
confidence: 99%
“…Study populations were diverse among these studies. One study was performed totally with inpatients [27], another two consisted of a mixture of outpatients and inpatients [4,14], while the other two did not make clear statements in this regard [5,15]. P atients in the TA groups were treated with various anticoagulant protocols among the studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…One of them did not report specifi c anticoagulation drugs [5], and none of the three retrospective studies reported the duration of TA [4,5,27]. Notably, two prospective studies by Schwarz et al applied additional compression stockings in both the TA and control groups [14,15].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations